Judi Online Dan Watak Kriminal Perspektif Psikologi Kriminal - Fransisca Adline Mlati Dewi; Putri Nur Amaliya Sariman; Abiyadh Raissa Ramadhan; Muhammad Farhan; Tugimin Supriyadi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
The development of digital technology and increasingly widespread internet access in recent decades has led to a significant increase in online gambling participation. The ease of access offered by online gambling platforms has attracted a wide range of people regardless of age, gender, or socioeconomic background. However, this phenomenon also brings serious negative impacts, including addiction that can trigger criminal behaviour such as fraud, theft, and money laundering. This research aims to explain the relationship between online gambling and criminal behaviour from a criminal psychology perspective and discuss the social implications and effective prevention strategies. The method used is a literature study, with analysis of various data sources from books, journals, and previous research. The results of the review show that online gambling not only affects the economy, religion and mental health of individuals, but can also damage household harmony and social relationships. This study is expected to provide a deeper understanding of the dynamics of online gambling addiction and criminal behaviour so that more effective intervention approaches can be formulated.